1999
DOI: 10.1017/s1014233900003497
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Brazilian animal genetic resources conservation programme

Abstract: SummaryBrazil has various species of domestic animals which developed from breeds brought by the Portuguese settlers soon after the discovery. Over the last five centuries, these breeds have been submitted to natural selection in particular environments and therefore today, they present characteristics adapted to the specific environmental conditions. From the beginning of this century, some exotic breeds, selected in temperate regions, have begun to be imported. Although more productive, these breeds lack ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 4 publications
4
19
0
5
Order By: Relevance
“…This evidence suggested that the effective population number of the analyzed breeds might be considerably large. The highest F IS values observed for the specialized exotic breeds Guzerat and Holstein (Table 2) were consistent with the history of intense artificial selection within these populations (Mariante et al, 1999). The dendrogram based on the Nei DA genetic distance measures (Figure 1) presents the Senepol breed in an isolated clade among taurine populations.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This evidence suggested that the effective population number of the analyzed breeds might be considerably large. The highest F IS values observed for the specialized exotic breeds Guzerat and Holstein (Table 2) were consistent with the history of intense artificial selection within these populations (Mariante et al, 1999). The dendrogram based on the Nei DA genetic distance measures (Figure 1) presents the Senepol breed in an isolated clade among taurine populations.…”
Section: Discussionsupporting
confidence: 72%
“…The racial standards for zebuine breeds were only described and implemented in 1938 (Josahkian, 2000). Therefore, genetically pure herds directly descended from imported animals of both genders and without taurine gene introgression are very rare nowadays (Mariante et al, 1999). This last hypothesis was corroborated by the melted pattern of admixture observed for the zebuine breeds in Bayesian analysis conducted using STRUCTURE (Figure 2).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Os ovinos pantaneiros são oriundos de cruzamentos entre as raças que foram trazidas pelos colonizadores portugueses e espanhóis logo após o descobrimento (MARIANTE et al, 1999). Estes animais são encontrados em fazendas mais isoladas da região, sem nenhum controle reprodutivo ou sanitário, vivendo há muitos anos praticamente sob seleção natural (VARGAS JUNIOR et al, 2011).…”
Section: Introductionunclassified
“…Over the years, these breeds were subjected to natural selection of local environmental and edaphoclimatic conditions, resulting in breeds that are currently considered naturalized, locally adapted, or native (Mariante et al, 1999). Agricultural census data collected by the Brazilian Institute of Geography and Statistics put the Brazilian sheep population at more than 17 million animals, center mainly in the southern and northeastern regions of the country.…”
Section: Introductionmentioning
confidence: 99%